2016
DOI: 10.21767/1989-5216.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors associated with Hearing Impairment in Preschool Children in Albania

Abstract: Background: Hearing impairment (HI), a condition that affects disproportionally children in developing countries, could negatively impact the development of communications skills of involved children when not timely detected and treated. Aims:We aimed to assess the prevalence of HI and the factors and health conditions associated with it, among preschool children in Albania. Study design:Cross-sectional survey.Methods: During November 2009-May 2011 a simple random sample of 400 preschool children aged 4-6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Missing out on diagnosing HI in children might negatively affect the future development of speech, language and communications skills as well as their academic performance. 8 Furthermore, HI can put children at higher risk of physical, social and emotional abuse and later during adulthood it can be associated with feeling embarrassed, loneliness, social isolation, abuse, depression, uneasy relationships, low career opportunities and low earnings.…”
Section: Hearing Assessment In Chronic Adenotonsillitismentioning
confidence: 99%
See 1 more Smart Citation
“…Missing out on diagnosing HI in children might negatively affect the future development of speech, language and communications skills as well as their academic performance. 8 Furthermore, HI can put children at higher risk of physical, social and emotional abuse and later during adulthood it can be associated with feeling embarrassed, loneliness, social isolation, abuse, depression, uneasy relationships, low career opportunities and low earnings.…”
Section: Hearing Assessment In Chronic Adenotonsillitismentioning
confidence: 99%
“…Early detection of HI [in preschool children] and subsequent corrective measures can improve school attainment and communication skills. 8 A study among 1528 preschool children aged 2-7 years suggested that children with mild hearing loss (20-40 dB) had significantly more phonologic, grammar and vocabulary problems compared to normal hearing children (<20 dB), suggesting that even mild hearing loss could be detrimental. 18 Therefore, the detection and treatment of even mild HI is important in order to prevent the adverse effects associated with it.…”
Section: Hearing Assessment In Chronic Adenotonsillitismentioning
confidence: 99%